A Unidirectional Voltage Vector Preselection Strategy for Optimizing Model Predictive Torque Control With Discrete Space Vector Modulation of IPMSM - Alsofyani, Ibrahim Mohd; Lee, Kyo Beum (IEEE Transactions on Industrial Electronics, 2022)
Discrete space vector modulation (DSVM) is employed to synthesize large number of voltage vectors (VVs) to improve the steady-state performance of predictive torque control (PTC). However, enumerating all the VVs in the prediction process increases the computation load of the motor drive. To address this issue, this article proposes a unidirectional VV preselection (UVVP) method for optimizing the performance of DSVM-based PTC of ac motors. The proposed UVVP method divides both voltage space vector diagram (VSVD) and flux space trajectory into twelve 30° based sectors to reduce the impact of candidate VVs with negative effects. At each flux position, the UVVP strategy can restrict the nearest candidate VVs in the 30° based VSVD region within the circular flux trajectory. This is achieved by using the speed direction to avoid the candidate VVs, which are in the same flux sector for reverse flux rotation, hence resulting in significant flux and torque ripple reduction. The main benefit of the proposed method is its simplicity since it only requires the flux sector and speed information as well as it can generate the VV enumerations online while ensuring the reduction of computation burden.
Keywords: Aerospace electronics; Discrete space vector modulation; Discrete space-vector modulation; Permanent magnet synchronoi machine; Permanent magnets synchronous machines; Pre-selection; Predictive torque control; Predictive torque controls; Steady state; Voltage vectors; Discrete space vector modulation (DSVM); permanent magnet synchronous machine (PMSM); predictive torque control (PTC)